‘Queer Natures’: Feminist Ecocriticism, Performativities, and Ellen van Neerven’s “Water” - Samuele Grassi (Lea, 2017)
This paper brings together queer ecological thought, ecofeminism, and feminist ecocriticism to explore forms of embodied resistance against intersectional, complex oppressions of women, races, and lands. It looks at the award-winning Indigenous Australian writer Ellen van Neerven’s short story, “Water” (from the 2014 collection, Heat and Light) to canvas an anti-essentialised queer feminist politics and ethics of care through which to shape utopian futures after sovereignty, after the West, after patriarchy, after whiteness.